2016
DOI: 10.1002/brb3.503
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions of the cortical networks during thought suppression

Abstract: ObjectivesThought suppression has spurred extensive research in clinical and preclinical fields, particularly with regard to the paradoxical aspects of this behavior. However, the involvement of the brain's inhibitory system in the dynamics underlying the continuous effort to suppress thoughts has yet to be clarified. This study aims to provide a unified perspective for the volitional suppression of internal events incorporating the current understanding of the brain's inhibitory system.Materials and MethodsTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 95 publications
(207 reference statements)
4
6
0
Order By: Relevance
“…A GLM analysis (see Materials and Methods for details) revealed a left-lateralized network was associated with imagery production and a right-lateralized network associated with suppression ( Figure 2A). This is consistent with previous neuroimaging and lesion studies (Farah 1984;D'Esposito et al 1997;Aso et al 2016;Garavan, Ross, and Stein 1999). The brain areas activated by both imagery (on the left hemisphere) and suppression (on the right hemisphere) were the superior frontal, prefrontal and temporal cortex (Figure 2A).…”
Section: Imagery and Suppression Engage Differently Lateralized Netwosupporting
confidence: 91%
“…A GLM analysis (see Materials and Methods for details) revealed a left-lateralized network was associated with imagery production and a right-lateralized network associated with suppression ( Figure 2A). This is consistent with previous neuroimaging and lesion studies (Farah 1984;D'Esposito et al 1997;Aso et al 2016;Garavan, Ross, and Stein 1999). The brain areas activated by both imagery (on the left hemisphere) and suppression (on the right hemisphere) were the superior frontal, prefrontal and temporal cortex (Figure 2A).…”
Section: Imagery and Suppression Engage Differently Lateralized Netwosupporting
confidence: 91%
“…Moreover, increased fluctuation during suppression was found in this frontoparietal network [50], with re-emergence of intrusive thoughts being associated with activation of the ACC [49]. These findings corroborate the difficulty of intrusive thoughts management through suppression maintenance.…”
Section: Experiential Avoidancesupporting
confidence: 72%
“…Thought suppression involves continuous inhibition and, in healthy controls, seems to be related to activity in the DLPFC [49], with extension to the right lateral frontoparietal network [50], suggesting a coordinated engagement of the executive control and dorsal attention networks. Moreover, increased fluctuation during suppression was found in this frontoparietal network [50], with re-emergence of intrusive thoughts being associated with activation of the ACC [49].…”
Section: Experiential Avoidancementioning
confidence: 97%
“…This region is part of the Frontoparietal Control Network (FCN), a network that may act as intermediary between DAN and Default Mode networks ( Vincent et al, 2008 ). Studies have found the region to have increased activation of the IPL during tasks that require inhibition of responses, such as the stop signal task ( Aron and Poldrack, 2006 ) and suppression of visual response ( Aso et al, 2016 ). This region has also been associated with multi-modal sensory information integration ( Beauchamp et al, 2010 ; Gentile et al, 2011 ; Renier et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%